Force control of twisted and coiled polymer actuators via active control of electrical heating and forced convective liquid cooling. (18th July 2018) - Song, Hyungeun; Hori, Yoichi
ABSTRACT: For decades, numerous artificial muscles have been proposed in order to implement beneficial features of biological muscles into robotics. Unfortunately, traditional artificial muscles experienced difficulties in imitating properties of the biological muscles due to mechanical and control issues. Recently, twisted and coiled polymer actuators (TCP) have been shown to produce large mechanical power via thermal stimulations and strong linearity. In this paper, a high-performance TCP thermally cycled by electrical heating and forced convective liquid cooling is designed and associated control algorithms are presented. We elaborate the model of the TCP that is simple, yet provides insight into how the electrical heating and the forced convective liquid cooling contribute to the TCP actuation. The proposed model is verified by experimental studies. Based on the proposed model, we design a feedforward–feedback controller and switching laws, which actively control the TCP in both the heating and cooling cycles. Furthermore, we extend our control methodology to agonist–antagonist TCPs. From the experimental studies, the proposed method is shown to be effective in both single TCP and antagonistic TCPs. GRAPHICAL ABSTRACT: